Characterizing the Need for Multiple Epidural Blood Patches in the Treatment of Postdural Puncture Headache: An Observational Study. Issue 3 (24th September 2022) - Mustafa, R.; Barman, R.; Kurian, E.; Eldrige, J.; Frank, R.; Kissoon, N.; Garza, I.; Whealy, M.; Cutsforth-Gregory, J.; Olatoye, O.
Abstract : ( Reg Anesth Pain Med . 2021;46:1110–1112) Previous studies have determined the effectiveness of epidural blood patch (EBP) on postdural puncture headache (PDPH) patients, though little research has been done on repeated image guided EBP. This study aims to predict the factors contributing to and the rate of repeated image-guided EBP treatment for (PDPH) patients.